Pharmacological targeting of host chaperones protects from pertussis toxin in vitro and in vivo - Ernst Katharina; Mittler Ann-Katrin; Winkelmann Veronika; Kling Carolin; Eberhardt Nina; Anastasia Anna; Sonnabend Michael; Lochbaum Robin; Wirsching Jan; Sakari Moona; Pulliainen Arto T; Skerry Ciaran; et al. (NATURE RESEARCH, 2022)
Whooping cough is caused by Bordetella pertussis that releases pertussis toxin (PT) which comprises enzyme A-subunit PTS1 and binding/transport B-subunit. After receptor-mediated endocytosis, PT reaches the endoplasmic reticulum from where unfolded PTS1 is transported to the cytosol. PTS1 ADP-ribosylates G-protein alpha -subunits resulting in increased cAMP signaling. Here, a role of target cell chaperones Hsp90, Hsp70, cyclophilins and FK506-binding proteins for cytosolic PTS1-uptake is demonstrated. PTS1 specifically and directly interacts with chaperones in vitro and in cells. Specific pharmacological chaperone inhibition protects CHO-K1, human primary airway basal cells and a fully differentiated airway epithelium from PT-intoxication by reducing intracellular PTS1-amounts without affecting cell binding or enzyme activity. PT is internalized by human airway epithelium secretory but not ciliated cells and leads to increase of apical surface liquid. Cyclophilin-inhibitors reduced leukocytosis in infant mouse model of pertussis, indicating their promising potential for developing novel therapeutic strategies against whooping cough.